Associations between private speech, behavioral self-regulation, and cognitive abilities. (November 2015) - Aro, Tuija; Poikkeus, Anna-Maija; Laakso, Marja-Leena; Tolvanen, Asko; Ahonen, Timo
We examined the associations between 5-year-old children's private speech, behavioural self-regulation, and cognitive abilities. Behavioural self-regulation was assessed using parental and preschool teacher questionnaires. Cognitive abilities (i.e., language, inhibition, planning and fluency, and memory) were assessed with neurocognitive tests, and the effectiveness of private speech (i.e., whether the child performs better when using speech than when not using speech) with the Hammer Task. About 43% of the children used private speech spontaneously, and about 76% performed better on the Hammer Task when they used speech. Associations between behavioural self-regulation and speech effectiveness were few, but all cognitive scores were significantly associated with the speech effectiveness score, i.e., the poorer the child's neurocognitive test performance was, the more he/she benefited from using speech. The findings lend support to the relevance of children's cognitive abilities when seeking understanding on the development, use, and effectiveness of private speech.